Decision Support System for The Purchase of A Printer in Hi-Tech Mall Method Using Fuzzy Tahani - Sutrisno; Eko Prasetyo; Rani Purbaningtyas (JEECS (Journal of Electrical Engineering and Computer Sciences), 2016)
With the availability of many brands and types of printers sold by shops in hi-tech Mall resulted in consumers ' difficulties in selecting the printer as needed. In addition, the seller is also complicated in helping consumers to choose the printer that will be purchased. The existence of this, research is trying to build a printer purchase decision support system using fuzzy method tahani implemented in the form of an informative website. The printer then purchase SPK tested to 15 people the user is divided into 5 testing query, where on every test there are three categories i.e. inkjet, color laser and laser mono. Furthermore, the results of these tests are compared with the opinion of the user regarding the printer that match criteria you selected, and the obtained results of 67% user opinions match up with the results of the recommendation given by the system.